(untitled) (Bangladesh Journal of Botany, 2024)
This study explored the changes in carbon components of tobacco-planting soil by the application of rice straw as organic materials to replace chemical fertilizers partially. Flue-cured tobacco was applied to the soil as base fertilizer to investigate the mineralization of soil organic carbon during its growing period. At 0 d, the humic acid carbon (HA-C), humin carbon (HM-C), HU ratio, PQ value and HM-C/(HA-C + FA-C) are 31.67, 31.40, 60.05, 28.01 and 27.75%, respectively which is higher than those of chemical fertilizer alone. At 30 d, the humus carbon (HE-C), HA-C, and fulvic acid carbon (FA-C) were 29.41, 20.97 and 30.49%, respectively. At 90 d, the A2920/1630 values were 227.43 and 232.32% higher than chemical fertilizer. Application of rice straw and decomposed rice straw with less fertilizer can increase the content of soil organic matter, HA-C, HM-C and FA-C in the tobacco-planting soil. This method increases the content of aliphatic chain hydrocarbons and reduces the amount of aromatic carbon, thus increasing aliphatic properties and decreasing the aromatic properties of soil. The treatment with chemical fertilizer reduction with decomposed rice straw also accelerates the formation and accumulation of stable components such as humic acid and humin and significantly improves the humification of soil humus. Bangladesh J. Bot. 53(3): 811-822, 2024 (September) Special